Pengaruh Fasilitas dan Kualitas Layanan terhadap Kepuasan Pengguna Laboratorium Komputer FEBI UIN K.H. Abdurrahman Wahid, Pekalongan - Nuzulul Nuzulul; Rizky Andrean (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
The provision of adequate infrastructure and optimal services is very important in supporting the effectiveness of academic activities, including in the context of computer laboratories as a means of supporting student learning. This study aims to examine the effect of facilities and service quality on user satisfaction of computer laboratories at FEBI UIN K.H. Abdurrahman Wahid Pekalongan. This study uses a quantitative approach by distributing Likert-sized questionnaires to 119 respondents who are students who use computer laboratories. In analyzing the data using multiple linear regression techniques to determine whether there is an influence of facility variables and service quality on user satisfaction using IBM SPSS 27 tools. The results of the study show that facilities significantly affect user satisfaction, where the t count of the facility variable is 5.397 > t table of 1.980 and a significance value of 0.000 <0.05. Service quality significantly affects user satisfaction, where the t count is 4.918 > t table of 1.980 and a significance value of 0.00 <0.05. Simultaneously, shared facilities and service quality influence user satisfaction, with the calculated F-value of 90.196 exceeding the F-table value of 3.07, with a significance level of 0.00 < 0.05.